PROFIL PENYELESAIAN MASALAH MATEMATIKA SISWA SMA DITINJAU DARI PERBEDAAN JENIS KELAMIN - Asnur Ali; Pathuddin; Sutji Rochaminah; Sukayasa (Universitas Tadulako, 2021)
This study aims to describe the profile of students' mathematical problem solving in terms of gender differences. This type of research is descriptive research using a qualitative approach. The subjects of this study were students of class X SMA which consisted of one male student and one female student with high mathematical ability. The data were collected using the problem solving task method and the interview method. The results of this study include, female subjects can express verbally or in writing the information contained in the given task, the subject can develop a problem-solving plan by making an example to make a mathematical model in the form of an equation and want to solve it using a combined method, the subject carries out the settlement plan is in accordance with the problem solving plan, and the subject does not re-examine the problem solving because he does not understand how. While the male subject can verbally state the information contained in the given task, the subject can develop a problem-solving plan by making an example to make a mathematical model in the form of an equation and want to solve it using the combined method, the subject carries out a settlement plan according to the plan. problem solving, and the subject did not re-examine the problem solving because they did not know how.